Accounting Cost Determination Practices in Notary Office Company Establishment: Praktik Penetapan Biaya Akuntansi dalam Pendirian Perusahaan Kantor Notaris - Nur Ravita Hanun; Dewi Novita Sari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The growth of business entities has increased demand for legally established limited liability companies requiring notarial services and structured financial management. Specific Background Many notary offices still manage service fees without formal accounting records, relying on informal calculations. Knowledge Gap Limited studies describe how accounting practices are actually applied in determining company establishment costs within notary offices. Aims This study examines the mechanism of fee determination, the conformity of accounting practices, and the supporting and inhibiting factors in setting the cost of establishing a limited liability company at a notary office in Sidoarjo Regency. Results Using a descriptive qualitative approach with interviews, documentation, and data triangulation, findings show that the office does not apply full costing or variable costing, but adopts cost-based pricing combined with market considerations and flexible negotiation. Pricing relies on historical archives rather than systematic bookkeeping, making profit measurement uncertain. Novelty The research provides an in-depth case-based analysis integrating cost accounting and behavioral perspectives in notarial services. Implications The study highlights the need for structured accounting records to support accurate cost calculation, transparency, and better financial decision-making in professional legal service offices. Keywords: Cost Accounting, Notary Fees, Company Establishment, Pricing Strategy, Behavioral Accounting Key Findings Highlights: Pricing relies on historical archives and informal calculations Negotiated packages depend on social and economic considerations Absence of bookkeeping limits profit evaluation accuracy